Indication-specific pricing of pharmaceuticals in the US healthcare system. (July 2017) - Pearson, Steven D; Dreitlein, William B; Henshall, Chris; Towse, Adrian
Aim: To explore the potential of indication-specific pricing (ISP) of pharmaceuticals and to discuss prospects for implementation in the US healthcare system.Materials & methods: The Institute for Clinical and Economic Review convened a policy forum with 44 healthcare leaders from 22 payer and life sciences companies. Models of ISP were discussed.Results: Payers and drug manufacturers saw the potential benefits of an ISP system that balances affordability for payers, sustainability for manufacturers and access for patients. The US healthcare system presents many challenges to implementation, including potential conflicts with existing pricing policies (Medicaid Best Price, average sales price and 340B) and insufficient data systems and analytic capabilities.Conclusion: Possible solutions and policy recommendations for payers and manufacturers are provided.